2015
DOI: 10.3109/13813455.2015.1087033
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural vascular adaptations following 8 weeks of low volume high intensity interval training in lower leg of type 2 diabetes patients and individuals at high risk of metabolic syndrome

Abstract: HIIT induced an improvement of endothelium-dependent FMD and significant outwards artery modelling. No changes in circulating cell adhesion molecules were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 52 publications
0
31
1
3
Order By: Relevance
“…6.1 ± 1.8) in patients with T2D. In another study, Madsen et al. (2015) showed that after low‐volume HIIT, FMD increased more in healthy persons (41%) than in patients with T2D (23%).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…6.1 ± 1.8) in patients with T2D. In another study, Madsen et al. (2015) showed that after low‐volume HIIT, FMD increased more in healthy persons (41%) than in patients with T2D (23%).…”
Section: Discussionmentioning
confidence: 92%
“…Green, Spence, Halliwill, Cable, & Thijssen, 2011). Research in patients with T2D found that exercise training increased FMD in the brachial and popliteal artery (Francois & Little, ; Madsen, Thorup, Overgaard, Bjerre, & Jeppesen, ). Type 2 diabetes is associated with endothelial dysfunction as well as elevated retrograde SR (Gibbs et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…High intensity interval training (HIIT) has been proposed to be a time-efficient (low volume) method to improve aspects related to body composition and disease (Madsen et al, 2015a; Madsen et al, 2015b; Sijie et al, 2012; Talanian et al, 2007). Madsen et al (2015a) showed only a modest improvement in anti-inflammatory cytokine after eight weeks of HIIT for subjects at risk for metabolic syndrome individuals, while inflammatory cytokines did not change.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have demonstrated that, compared to aerobic exercise, HIT is more effective at improving insulin resistance (Jelleyman et al, 2015) and V O2max (Milanovic et al, 2015) in healthy sedentary individuals. In T2D patients, HIT has been shown to be associated with improvements in insulin sensitivity (Karstoft et al, 2014), glycaemic control (Little et al, 2011), and endothelial function (Madsen et al, 2015). However, due to the required recovery periods in between high-intensity bouts, most available HIT protocols are not as time-efficient as often claimed (Gillen & Gibala, 2014), and even in submaximal HIT protocols the high number of high-intensity bouts per training session results in high perceived exertion (Little et al, 2011).…”
Section: Introductionmentioning
confidence: 99%